1996
DOI: 10.1007/bf00199509
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of urokinase-type plasminogen activator (uPA) and plasminogen activator inhibitors PAI-1 and PAI-2 in gastric cancer

Abstract: Expression of urokinase-type plasminogen activator (uPA), plasminogen activator inhibitor-1 (PAI-1) and plasminogen activator inhibitor-2 (PAI-2) was evaluated in 125 surgically resected gastric cancers by immunohistochemical analysis. Tissue was stained immunohistochemically with a monoclonal antibody against human uPA and monoclonal antibodies against human PAI-1 and PAI-2. In addition, DNA ploidy patterns were determined by cytofluorometer after staining with propidium iodide. We found that 82 (66%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…23,24 PAI-2 immunoreactivity in the metastases of stage III and IV ovarian cancer was predictive of a prolonged disease-free and overall survival, 35 whereas PAI-2 immunoreactivity in tumor tissue of gastric cancer was not associated with prognosis. 36 Our finding in endometrial cancer is thus in agreement with reports in colorectal cancer and with some studies of ovarian cancer. In contrast, several studies in breast cancer have indicated that high tumor tissue concentrations of PAI-2 are associated with better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…23,24 PAI-2 immunoreactivity in the metastases of stage III and IV ovarian cancer was predictive of a prolonged disease-free and overall survival, 35 whereas PAI-2 immunoreactivity in tumor tissue of gastric cancer was not associated with prognosis. 36 Our finding in endometrial cancer is thus in agreement with reports in colorectal cancer and with some studies of ovarian cancer. In contrast, several studies in breast cancer have indicated that high tumor tissue concentrations of PAI-2 are associated with better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Some reports have indicated that PAI-2 expression in gastric tumors was associated with decreased metastasis (15) and was significantly higher in patients without lymph node involvement (43). In contrast, other reports have indicated either that PAI-2 expression was not related to prognosis (16) or was an indicator of recurrence (17). The reasons for these differences have been uncertain, and we now suggest that they reflect the balance between the effects of secreted and intracellular PAI-2.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have established that uPA and the inhibitors PAI-1 and PAI-2 are expressed in gastric adenocarcinoma (15)(16)(17). In the present study, we asked whether H. pylori infection was associated with changes in gastric PAI-2 expression.…”
Section: Introductionmentioning
confidence: 87%
“…Clinical results reveal that a lower level of SERPINB2 expression is associated with poor prognosis and outcome in gastric (8,9), breast (10) and lung cancers (11 to completely inhibit soluble and cell-surface bound plasminogen activator activity, resulting in the suppression of the metastasis of melanoma cells in SCID mice (12). SERPINB5 (MASPIN) has been well studied and was confirmed to be a tumor-suppressor gene, which suppresses tumor growth, invasion and metastasis in different types of cancers, and has potential therapeutic perspectives (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%